Islamic Civilization and Culture and Present Era: اسلامی تہذیب و ثقافت اور عصر حاضر - Khan , Dr. Muhammad Iqbal; Naz, Dr. Hina; Sadiq, Dr. Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
“No doubt, culture and civilization is not confined to one sector but development of culture and civilization refers the standard of living of that society. In every age, different movements were started by the promotion specific culture. As concerned Islamic Culture it has static culture in every age. This Culture has advantage over all other cultures because its values are based on divine principles rather than man made principle which have short comings. Therefore, it is needed to promote Islamic Culture which has ability to solve the social and cultural problems of each and every society. https://doi.org/10.5281/zenodo.10519299